2013
DOI: 10.2528/pierb13092206
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-Dipolar-Mode Oscillations for Near- And Far-Field Manipulation of Microwave Radiation

Abstract: Abstract-There has been a surge of interest in the subwavelength confinement effects of the electromagnetic fields. Based on these effects, one can obtain new behaviors of the near-and far-field radiation.It is well known that in optics, the subwavelength confinement can be obtained due to surface-plasmon (or electrostatic) oscillations in metal structures. This paper is a review of recent studies on the subwavelength confinement in microwaves due to magnetic-dipolar-mode (MDM) [or magnetostatic (MS)] oscillat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Generating far-field orbital angular momenta from near-field microwave chirality of MDM structures can be a subject of great interest. Realization of such vortex generators opens the perspective for far-field microwave systems with topological-phase modulation [46].…”
Section: Discussionmentioning
confidence: 99%
“…Generating far-field orbital angular momenta from near-field microwave chirality of MDM structures can be a subject of great interest. Realization of such vortex generators opens the perspective for far-field microwave systems with topological-phase modulation [46].…”
Section: Discussionmentioning
confidence: 99%
“…From literature, one can see that for the MDM spectral problem formulated exceptionally for the MS-potential wave function ( , ) rt  , no use of the alternative electric fields is presumed [20 -22, 37 -39]. Following a formal analysis [40,41] it can be also shown that for MDM oscillations, the Faraday equation is incompatible with Eqs. (1) and (2 [42] it was merely stated that in a case of the MDM spectral problem, an electric field is completely absent and thus 0 E    .…”
Section: A Magnetostatic Description and Faraday Lawmentioning
confidence: 99%